2016
DOI: 10.1007/s11701-016-0570-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining clinical outcomes utilizing low-pressure pneumoperitoneum during robotic-assisted radical prostatectomy

Abstract: The objective of the study was to assess the safety and clinical outcomes of performing RARP utilizing LPP 12 mmHg with locally confined adenocarcinoma of the prostate. Utilizing the Metro Health RALP database registry and the Michigan Urological Clinic records, we retrospectively reviewed the records of consecutive RALPs performed between December 2012 and March 2015 by a single robotic surgeon. 100 patients underwent RARP utilizing 15 mmHg of standard pressure pneumoperitoneum (SPP) and 100 patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
(8 reference statements)
0
17
0
2
Order By: Relevance
“…Christensen and colleagues compared a pressure of 12 mmHg versus 15 mmHg, following a retrospective review of their single surgeon prostatectomy database from 2012 to 2015 [ 7 ]. 100 patients who had prostatectomy at 15 mmHg and then 100 who had prostatectomy at 12 mmHg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Christensen and colleagues compared a pressure of 12 mmHg versus 15 mmHg, following a retrospective review of their single surgeon prostatectomy database from 2012 to 2015 [ 7 ]. 100 patients who had prostatectomy at 15 mmHg and then 100 who had prostatectomy at 12 mmHg.…”
Section: Resultsmentioning
confidence: 99%
“…Rohloff and colleagues performed a retrospective review of 400 patients undergoing prostatectomy over a 5-year period. A single surgeon (the same as in the Christensen et al paper [ 7 ]) performed 209 successful prostatectomies at 15 mmHg of which, 202 were included in the study [ 8 ]. The same surgeon then changed practice and performed the remaining 198 prostatectomies at 12 mmHg which were included as the second arm of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Christensen et al. compared postoperative outcomes of 200 RALP procedures (100 performed at a standard pressure of 15 mmHg and 100 at a pressure of 12 mmHg), finding no significant differences in LOS or complications. La Falce et al.…”
Section: Discussionmentioning
confidence: 99%
“…Christensen et al [15] compared postoperative outcomes of 200 RALP procedures (100 performed at a standard pressure of 15 mmHg and 100 at a pressure of 12 mmHg), finding no significant differences in LOS or complications. La Falce et al [7] performed 53 RALP procedures at 8 mmHg and found improvements in multiple intra-operative cardiovascular variables but did not assess postoperative outcomes such as pain scores and LOS.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Postoperative ileus is caused by many factors, the most important of which is the preferred surgical technique. Christensen et al [17] divided their patients into two groups and performed robotic radical prostatectomy by applying the 12 mmHg pressure in one group and 15 mmHg in the other. Postoperative ileus was detected in 4% of the low pressure group, whereas it was detected in 8% of the other group.…”
Section: Discussionmentioning
confidence: 99%